Inflammation-frailty linkage and its long-term prognostic impact in patients with acute coronary syndrome. (14th October 2021) - Satou, R; Matsuzawa, Y; Akiyama, E; Konishi, M; Yoshii, T; Nakahashi, H; Minamimoto, Y; Okada, K; Maejima, N; Iwahashi, N; Hibi, K; Kosuge, M; et al.
Abstract: Introduction: Chronic inflammation has been receiving considerable attention as an emerging risk factor for cardiovascular disease. In contrast, with the aging of the population, frailty has been also attracting a great deal of attention as the residual risk for cardiovascular disease. Although inflammation and frailty exacerbate each other and have an adverse effect on many diseases, the relationship between chronic inflammation and frailty and the impact of these combination on long-term prognosis in patients with acute coronary syndrome (ACS) are not elucidated. Purpose: The aims of this study were to determine the association between chronic inflammation and frailty and its impact on long-term cardiovascular outcomes in patients with ACS. Methods: A total of 482 consecutive ACS patients with obstructive coronary artery disease (age 66±12 years, male 81%) were enrolled in this observational study. We evaluated patients' gait speed as a measure of frailty before discharge. C-reactive protein (CRP) levels at 1 month after discharge were also evaluated as inflammation in the chronic phase. According to commonly used criteria of the residual inflammation (CRP>0.2 mg/dL) and the definition of the European Working Group for Sarcopenia (gait speed ≤0.8 m/sec), patients were stratified by 4 subgroups: low/high CRP with slow/normal gait speed. The primary endpoint was composite outcomes of cardiovascular death, myocardial infarction and ischemic stroke. Results: While there was no significant association between CRP levels and gait speed in all patients, a significant negative association between two variables was observed in the high CRP group (Spearman's ρ = −0.31, p=0.001). During the median follow-up of 6 years, primary endpoints have occurred in 82 patients. Overall, event-free rates differed significantly among the 4 groups, demonstrating the lowest event-free rate in the patients with high CRP and slow gait speed (p<0.0001; Figure). In the multivariate analysis, high CRP (adjusted HR 1.99, 95% CI 1.14–3.46, p=0.02) and slow gait speed (adjusted HR 1.82, 95% CI 1.09–3.04, p=0.02) were independently and significantly associated with the primary endpoint. Moreover, the patients with both high CRP and slow gait speed had a 2.6-fold higher risk of cardiovascular events compared to others (adjusted HR 2.62, 95% CI 1.36–5.05, p=0.004). Conclusion: In the patients with ACS, CRP levels and gait speed were negatively associated in the high CRP group. Chronic inflammation and frailty were both associated with poor prognosis in ACS and in particular, the combination of these factors was strongly associated with poor prognosis. Funding Acknowledgement: Type of funding sources: None.